Effects of deer age on the physicochemical properties of deproteinized antler cancellous bone: an approach to optimize osteoconductivity of bone graft. (4th June 2015) - Meng, Song; Zhang, Xuehui; Xu, Mingming; Heng, Boon Chin; Dai, Xiaohan; Mo, Xiaoju; Wei, Jinqi; Wei, Yan; Deng, Xuliang
Abstract: Inorganic bone xenograft materials have recently found extensive surgical application in the clinic. Previously we have demonstrated that calcinated antler cancellous bone (CACB) has great potential for bone defect repair, due to the similar structure and composition compared with human bone. However, the effect of intrinsic material characteristics, particularly deer age, on the physicochemical and biological properties of CACB scaffolds has not been clarified. The aim of this study is to investigate the structure, composition and in vitro solubility of CACB scaffolds derived from deer of varying ages, including young (CACB-Y), middle-aged (CACB-M), and old (CACB-O) deer, and to determine subsequent biological performance. Microstructural analyses showed looser crystal arrangement and lower porosity in CACB-M compared to CACB-Y and CACB-O. Phase-structure analysis showed that CACB-M had the largest crystal size. Component characterization results showed that CACB-M had the most carbonated substitute and the highest content of trace elements (Na, Fe). The in vitro solubility test showed that CACB-M had the fastest dissolution and apatite deposition rates with new crystalline phases. In addition, CACB-M could be conducive for attachment, proliferation and osteogenic differentiation of rat bone marrow mesenchymal stem cells in vitro, as well as conducive for bone regeneration in vivo . These findings indicate that animal age should be seriously considered as a key parameter in optimizing the physicochemical and biological properties of deproteinized antler cancellous bone substitutes for bone regeneration applications.